P180 Cause-specific and trend of mortality analysis in patients with inflammatory bowel disease: a Taiwanese Nationwide population-based study. (25th January 2019) - Wei, S C; Lin, W C; Weng, M T; Tung, C C; Chang, Y T; Leong, Y L; Wang, Y T; Wang, H Y; Wong, J M
Abstract: Background: Our previous study reported a higher mortality rate from inflammatory bowel disease (IBD) in Taiwan than in Western countries. With advancement in diagnosis and treatment for IBD, we proposed to compare the trend of mortality change and analyse cause-specific mortality in Taiwan. Methods: This retrospective study was conducted to analyse data for January 2001 to December 2015 from a registered database, compiled by the Taiwan's National Health Insurance. Results: Between 2001 and 2015, a total of 3806 IBD patients [Crohn's disease (CD): 919; ulcerative colitis (UC): 2887] were registered as having catastrophic illness, and 8.2% of these patients died during follow-up. The overall mortality rates for CD and UC were 20.0 and 10.8 per 1000 person-years, respectively. The standardised mortality ratios (SMRs) of CD and UC were 3.72 (95% CI: 3.02–4.55) and 1.44 (95% CI: 1.26–1.65), respectively, from 2001 to 2015, respectively (Table 1, Figure 1). A comparison of the periods of 2011–2015 and 2001–2005 revealed a decrease in the mortality rates from both UC and CD (Figure 2). Regarding cause-specific mortality in IBD patients, elderly individuals; comorbidities such as hypertension, diabetes, and chronic obstructive pulmonary disease; infections; IBD-related complications; malignancies; and surgeries were the risk factors for mortality (Table 2). Conclusions: In this nationwide population-based Taiwanese study, although SMRs of IBD patients decreased from 2001 to 2015, they were still higher than those of the general population. For further decreasing IBD-related mortality in Taiwan, we need to pay special attention towards elderly individuals, infection control, and improvement in perioperative care.